Analysis of Kentucky's Law Protecting the Rights of Schoolchildren With Type 1 Diabetes Mellitus: Application of Kingdon's Policy Stream Model. (February 2016) - Culp-Roche, Amanda; Adegboyega, Adebola
Type 1 diabetes mellitus is a chronic, life-threatening disorder that affects children of all ages. Based on data from 2008 to 2009, the Centers for Disease Control and Prevention estimates that in the United States, 191, 986 youth younger than age 20 require treatment for diabetes, the majority of whom have Type 1 diabetes mellitus. These children require assistance with counting carbohydrates, testing blood glucose, and administering subcutaneous insulin. Establishing appropriate diabetes care models in schools is necessary for children's immediate safety, long-term well-being, and optimal academic performance. Kentucky House Bill 98 was passed by the state legislature in 2014 to allow unlicensed school personnel to assist children with diabetes care. The purpose of this article is to apply Kingdon's policy streams model to an analysis of a state policy allowing unlicensed school personnel to assist children with diabetes care. The article covers potential policy alternatives and concludes with a discussion of implications for nursing practice.